Criminalization of Criminal Acts Based on Living Law in Regional Regulations in Indonesia - ., Syamsuddin; ., Hartiwiningsih; Rustamaji, Muhammad (Journal of Ecohumanism, 2024)
Indonesian criminal law is guided by the principles of justice, humanity and legal certainty. Some of these principles are universally accepted and applied at both national and international levels. From a historical perspective, Indonesia also adheres to multicultural principles which emphasize the philosophy of pluralism in the modern criminal legal system. However, in fact, the current reform of modern criminal law has many obstacles and challenges, where the principle of legality is sometimes not in line with the principles of living law, the application of criminal law based on local wisdom is still partial so there is room for the community to resolve the case there is no crime through local culture.Research purposes, want to know the existence of living laws (living law) seen from the perspective of sociological jurisprudence and national criminal law, also want to know the reformulation of crime-based crimes living law through regional regulations in Indonesia. Research methods, in the form of research normative law with a philosophical approach (philosophical approach) law, conceptual approach (conceptual approach), case (case), and the historical approach (historical approach).Results Study, shows that the national criminal law has progressively adapted to the values, social norms, culture, dynamics and social change, including the harmonization of criminal law regulations national with living laws (living law) as well as adapting social norms to developments and changes crime in society. Reformulation of criminal acts in regional regulation semphasizes the existence of principles of living law in the formulation of regional laws and regulations, the formation of law regions are adapted to the development of variations in crime in local communities, Local criminal law is a relevant solution in handling criminal cases faced by people in an area.